ASSESSMENT OF SERUM LEVELS AS SENSITIVE thyroid stimulating hormone EARLY DETECTION OF CANCER THYROID - Prichilia Sarah Permadi; Made Ratna Saraswati (Universitas Udayana, 2013)
Enlargement of thyroid or goiter is a general clinical problem. These cases are 5-10% may come to thyroid nodule. Thyroid cancer is thyroid gland malignancy in nodule formed. Clinically, benign thyroid nodule is difficult to thyroid nodule malignancy. The assessment of Thyroid Stimulating Hormone sensitive (TSHs) serum usually does as a screening tool to detect the enlargement and malignancy of thyroid gland which is suspected. Increases of TSH serum have a correlation with the prevalence of thyroid cancer.